(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2020)
This paper illustrates the design and implementation of commercial strategies applied by a regional company in agribusiness, which offers solutions with added value to agricultural companies through multiservice. It can be observed that there is a logical coherence between its growth strategy and its positioning and differentiation strategy to offer multiservice with added value. This can be seen in the commitment of the company with the client offering him/her additional benefits such as: administrative and marketing solutions, communication, professional advice, financial support, etc. Likewise, the company has defined its long-term strategy to serve its target market in a greater geographical area. In this case, a deliberate and planned strategy with a horizon and goals to be achieved is observed. For this, the company has designed plans for 5 years. The management towards the achievement of the goals is quantified in annual budgets, which are controlled and evaluated. To carry out its strategy in multi-services with added value, the company has put in practice and disposed of financial, technological, and human resources, and the plant and equipment needed in three linked business units: commercialization of cereals and oilseeds, commercialization of agricultural inputs and associated sowing in third-party fields.